2021
DOI: 10.3389/fphys.2021.664991
|View full text |Cite
|
Sign up to set email alerts
|

Similar Pain Intensity Reductions and Trunk Strength Improvements Following Whole-Body Electromyostimulation vs. Whole-Body Vibration vs. Conventional Back-Strengthening Training in Chronic Non-specific Low Back Pain Patients: A Three-Armed Randomized Controlled Trial

Abstract: The aim of this multicenter trial was to compare the effects of whole-body electromyostimulation (WB-EMS) and whole-body vibration (WBV) with conventional back-strengthening training (CT) on changes in mean back pain intensity (MPI) and trunk strength in patients suffering from chronic non-specific low back pain (CNLBP). Two-hundred and forty CNLBP patients (40–70 years; 62% female) were randomly assigned to three intervention arms (WB-EMS: n = 80 vs. WBV: n = 80 vs. CT: n = 80). All training intervention prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 42 publications
(56 reference statements)
0
30
0
1
Order By: Relevance
“…[39] Among the 26 studies included, 11 have been conducted with women only [16,20,[35][36][37][38][39][42][43][44][45] and 7 were only with men. [13,26,41,[46][47][48][49][50] Two interventions have been performed in patients with chronic low back pain, [34,51] 4 in people with sarcopenia and obese, [20,39,46,52] 4 in pre-and post-menopausal women [43][44][45]53] and 1 in older people with osteoarthritis. [38] Two studies have worked with athletes.…”
Section: Characteristics Of the Studies And Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] Among the 26 studies included, 11 have been conducted with women only [16,20,[35][36][37][38][39][42][43][44][45] and 7 were only with men. [13,26,41,[46][47][48][49][50] Two interventions have been performed in patients with chronic low back pain, [34,51] 4 in people with sarcopenia and obese, [20,39,46,52] 4 in pre-and post-menopausal women [43][44][45]53] and 1 in older people with osteoarthritis. [38] Two studies have worked with athletes.…”
Section: Characteristics Of the Studies And Participantsmentioning
confidence: 99%
“…However, 5 working groups used a maximum impulse tolerance appro ach. [35,38,39,48] and a single article worked the stimulus intensity between 80 and 100 mA. [21] It remains important to note that none of the studies reported negative side effects of WB-EMS applications Table 3.…”
Section: Wb-ems Protocol Usedmentioning
confidence: 99%
“…WBV effects have also been extensively documented at the musculoskeletal level, suggesting among the main benefits are an increase in bone mineral density and muscle mass and strength, as well as improved motor performance and general health [ 11 , 12 ]. Furthermore, WBV is currently used as a preventive tool for several diseases, such as osteoporosis, sarcopenia, and chronic low back pain, as well as for improving muscle function and joint stability [ 13 , 14 , 15 ]. In this context, we recently investigated the effects of WBV on skeletal muscle in a group of 12-month-old mice by light and electron microscopy, observing significant variations depending on the vibratory training protocol used [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the stimulation setting, NMES-as the underlying technology of WB-EMS application-has an impact on deeper muscle groups/layers [2], possibly contributing to the positive effects of WB-EMS on low back pain [7][8][9]. The neuro-muscular principle of (N)EMS is to predominately activate motor neuron axons or intramuscular axonal branches [10], which in turn stimulate the corresponding muscle fibers, allowing innervation of muscles along the neural tracts.…”
Section: Introductionmentioning
confidence: 99%